Career paths and employability competencies of young national and immigrant people at risk of social exclusion - Santana Vega, Lidia E.; Alonso Bello, Estefanía; Feliciano García, Luis (Revista Complutense de Educación, 2017)
Young people at risk of social exclusion have atypical career paths where they need to cope with marginalization; hence they need to acquire employability skills that allow them to obtain and maintain employment and participate in lifelong learning. The objectives of this work are: a) to analyze the employability skills of young nationals and immigrants leaving the public system of protection and b) to compare their career paths. A study of multiple cases took place. Four Young national and four unaccompanied young sub-Saharan immigrants at risk of exclusion, tutors of their centres and entrepreneurs who supervised the work placements participated in the study. The case selection took three criteria into account: 1) have been in residential care institutions, 2) have been in a job placement program for at least 6 months and 3) are 16-25 years of age. The study data were collected using qualitative and quantitative techniques and instruments. The results of the study show that: a) young immigrants develop a more realistic life design than young nationals; b) finish their social and professional integration program with a higher level of employability skills; c) cope with their transition to adulthood with a better educational level. The data obtained in the investigation show that young immigrants deal with the transition to adulthood in a more successful way than young nationals. We discuss the need to work on the objectives of the life design of young people at risk of exclusion, their support networks and their employability skills in order to consolidate their career paths.